Effect of Early Planting on Soybean Yield: 2021-2024 at Kansas River Valley - Eric Adee; Scott Dooley; Udit Debangshi; Gaurav Jha (Kansas Agricultural Experiment Station Research Reports, 2025)
To increase soybean yield potential, early planting dates have been promoted as a management practice that can increase the yield of soybeans. Early planting of soybeans can be a relative term, meaning late April/early May for some soybean producers in Kansas, but this study’s definition of early planted soybeans is late March/early April. Theoretically, the earlier planting date could allow for more vegetative growth and interception of more light before blooming, increasing the yield potential. With the improvement of soybean seed treatments to protect seeds when emergence is slowed due to cool and wet conditions, early planting may be a viable option. Over the four years this study has been conducted at the Kansas River Valley Experiment Field, the early planting dates in late March/early April have shown soybean yields as either stable or increased when planting in late March/early April compared to planting in mid-to-late April and early-to-mid May. This study also shows the increased yield potential compared to more traditional planting dates later in May.
Keywords: early planting; soybean